Disclosing HIV Status:Vis-avis Confidentiality, Right to Privacy and Public Interest - Salihu, Sani Ibrahim; Yusof, Yuhanif; Halim, Rohizan (Universiti Putra Malaysia Press, 2018)
Generally, privacy is a universally recognised human rights. In a medical setting, all patients have a right to privacy, while doctors have a corresponding duty. Doctors are entrusted with medical records or information of patients under their care. The information could be disclosed by the patient himself, created or generated by the doctors. Although this is a common law principle, sometimes it conflicts with the public interest and duty to warn a third party. However, health-related laws in Nigeria do not have an adequate provision ensuring the safeguard and protection of this rule, nor provide reconciliation where there is such conflict, like in the case of disclosing HIV status to spouses. The objective of this paper is to examine the law and the rules of medical practice on nondisclosure of a patient’s confidential record, with reference to doctors’ duty to keep confidential all information about their patient and the public interest, especially their HIV status. Doctrinal research method is used to study both primary and secondary legal resources. Reference may be made to other jurisdictions. The scope of the paper is limited to the provision of the legal framework regulating doctor-patient relationship in Nigeria. More than half of the HIV patients do not disclose their status to their spouses, and there is a conflict between patients’ right to privacy and public interest not to allow the spread of the viruses/ diseases due to nondisclosure principles. Hence, a need to have a legal framework to bridge this gap